PENGARUH PROFITABILITAS, LIKUIDITAS DAN LEVERAGE TERHADAP KEBIJAKAN DIVIDEN - Ditya Ayu Liestyorini, 06.05.52.0066; Fauzan, Fauzan (Students Journal of Accounting and Banking, 2012)
Dividend policy is the amount of revenue that will be given to investors. The purpose of this study was to examine and analyze the influence of profitability, liquidity and leverage, dividend policy. Based on selection criteria in this study found 25 companies, which generate 75 data pooling. Analytical methods used to analyze the influence of profitability, liquidity and leverage, dividend policy is a multiple linear regression analysis.The results of this study can be concluded that: (1) Return OnÂ nvestment (ROI) has a positive effect on the dividend payout ratio, meaning that the greater the ROI will increase the dividend payout ratio. (2) Current ratio is a positive influence on cash dividends, meaning that the higher the current ratio will increase the dividend payout ratio. (3) Debt to equity ratio does not affect the dividend payout ratioKeywords: profitability, liquidity, leverage and dividend policy